Interventions That Impact Aged Care Job Demands: A Systematic Review of Strategies and Their Evidence - Kho, Madison; Iles, Lucinda J.; Chong, J.X.Y.; Moore, Hayley I.; Andrei, Daniela; Parker, Sharon (American Psychological Association, 2025)
Intensifying job demands and their negative consequences are observed to a higher degree in aged care compared to health care and other sectors. However, the ability to identify and apply effective strategies to reduce job demands in this sector is impeded by a lack of synthesis and integration of existing research on interventions that directly or indirectly modify job demands. This article provides a systematic review of 68 interventions that provided data regarding implications for employee job demands in aged care. The most common strategies observed were professional education and client care protocol interventions. Cumulatively, these strategies provide moderately consistent evidence of reducing employee perceived demands and demands resulting from clients’ behavioral and psychological symptoms and client care, as well as improving employee work-related well-being and ill-being. Fewer studies investigated complex mixed-level and multicomponent interventions, potentially contributing to inconsistent evidence for their efficacy in reducing demands. This review highlights the potential for interventions to simultaneously address job demands and quality of client care, a relevant objective for health care industries. However, careful consideration of intervention effects on both these outcomes during and postimplementation is needed to maximize their benefit. More broadly, this review highlights the challenges in integrating interdisciplinary literature with relevant insights into the reduction of job demands, for job demand intervention researchers and practitioners, and provides guidance for further consolidation of existing and emerging research.